Dialectics of War as a Natural Phenomenon: Existential Perspective - Egbekpalu, Purissima Emelda; Oguno, Paschal Onyi; Alozie, Princewill (Conatus - Journal of Philosophy, 2023)
Due to natural processes of movements of opposites that interact with one another in equal forces, the universe is naturally considered an arena of conflicts. As the law of the universe continues to maintain everything in motion, each matter in the ecosystem strives to protect itself in given existential struggles within necessary conflicts. Therefore, the fundamental law of nature is the protection of life (self-preservation) which is often realized through self-defence. It then explains why humans engage themselves in conflicts; not necessarily to bring peace but to survive and maintain themselves in existence. Hence, war is motivated by the innate drive for self-defence and maintenance of self in existence guided by a natural instinct for survival. From conception to death, humans continue to struggle for survival and that entails overcoming conflicts and adversities of life. Thus, war can be considered as having a genetic foundation. This is evidenced in the works of evolutionary theorists. The Darwinian ethological theory tenaciously holds that humans, just like other organisms, struggle to survive, but this is influenced by natural selection which favours the stronger species against the weaker ones. While the stronger ones pass on their inheritable genes to the next generation for maintenance of their species in existence, the weaker ones die off. Hence, the survival of the fittest. This position was very much supported by the Malthusian theory of over-population alert against the limited human resources which demonstrates the constant fight for food in order to survive. The Nietzschean Superman, Marxian class struggle, Heraclitan notion of change, and so on, all cling to the idea that the universe is a violent arena. Consequently, the protection of life has an important moral value. By implication, self-defence is right and justified even if it involves war. Therefore, it is ethical to push through; to defeat the adversary.